Redes de cooperação entre EBTs do setor médico-hospitalar da região de São Carlos, Araraquara e Ribeirão Preto - Smolka, Rodrigo Bustamante (Universidade Federal de São Carlos, 2006)
Technology based firms (TBFs) and technology innovation process studies attract several fields of research. According to social networks concepts, the activities of organizations are affected by the relationship between them. This research aims to verify the existence of cooperation networks towards product innovation between TBFs in São Carlos, Araraquara and Ribeirão Preto from the medical and dental device industry and characterize their strength. In that sense, a study of the social network theory and its main concepts, TBFs and industry characteristics is carried out. The development of a methodology and analysis takes place. Variables such as strength of ties and network structure are considered in the analysis. Among the different actors in different networks, those with high centrality measure and importance are distinguished. Results show that cooperation ventures between TBFs are few, instead, many relations with universities and research institutes towards product development are present. Weak and strong ties can be found in this environment. Important actors that influence TBFs and the product development and innovation are market fairs, standardization agencies, trade associations and universities.
Keywords: Administração da produção; Análise de redes (Planejamento); Empresa de base tecnológica; Setor de equipamentos médico-hospitalar; Força da ligação; Índices de centralidade; Network analysis; Cooperation networks; Technology based firm; Medical and dental device industry; Strength of Ties; Centrality indexes; ENGENHARIAS::ENGENHARIA DE PRODUCAO